2020
DOI: 10.1186/s12873-020-0306-6
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on conveyance decision-making during emergency call outs to people with dementia: the HOMEWARD project

Abstract: Background: Paramedics are increasingly required to make complex decisions as to whether they should convey a patient to hospital or manage their condition at the scene. Dementia can be a significant barrier to the assessment process. However, to our knowledge no research has specifically examined the process of decision-making by paramedics in relation to people with dementia. This qualitative study was designed to investigate the factors influencing the decision-making process during Emergency Medical Servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Previous research on paramedic conveyance decisions for persons with dementia found that the person's clinical condition was the key factor [19]. The patient's circumstances, including the support available to them at home, were also recognised as important which reflects the results of this study.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Previous research on paramedic conveyance decisions for persons with dementia found that the person's clinical condition was the key factor [19]. The patient's circumstances, including the support available to them at home, were also recognised as important which reflects the results of this study.…”
Section: Discussionsupporting
confidence: 57%
“…Participants sometimes found that balancing guidelines and the best interests of the patient could be challenging. This mismatch of guidelines and clinical opinion has been found in previous research on UK paramedic conveyance decisions [19,24]. In particular, some participants reported they felt the NICE HI guidelines were less appropriate for frail patients.…”
Section: Discussionmentioning
confidence: 58%
“…This can make it challenging for those individuals to reach a phone to call for an ambulance or to go to the door to let ambulance crews in. Being bedridden or wheelchair-bound in some of these patients can furthermore complicate their ability to access ambulance services [52,53].…”
Section: Challenges In Ambulance Service Utilizationmentioning
confidence: 99%
“…Research on paramedic decision-making more broadly finds professional vulnerability and a fear of repercussions is a dominant theme with paramedics fearing disciplinary investigation and litigation in relation to managing patients who self-harm [ 14 ]; making non-conveyance decisions [ 18 21 ]; and cardiac arrest management [ 22 , 23 ]. More generally, there is anxiety around practice in what has been described as a ‘hostile environment’ of discipline and blame within UK ambulance services [ 24 ].…”
Section: Introductionmentioning
confidence: 99%